2014
DOI: 10.1186/1556-276x-9-101
|View full text |Cite
|
Sign up to set email alerts
|

In vivo synthesis of nanomaterials in plants: location of silver nanoparticles and plant metabolism

Abstract: Metallic nanoparticles (MeNPs) can be formed in living plants by reduction of the metal ions absorbed as soluble salts. It is very likely that plant metabolism has an important role in MeNP biosynthesis. The in vivo formation of silver nanoparticles (AgNPs) was observed in Brassica juncea, Festuca rubra and Medicago sativa. Plants were grown in Hoagland's solution for 30 days and then exposed for 24 h to a solution of 1,000 ppm AgNO3. In the leaf extracts of control plants, the concentrations of glucose, fruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 33 publications
3
75
0
Order By: Relevance
“…From the xylem, NPs can distribute within the rest of the plant and be loaded into the phloem. Nanoparticles in the xylem have often been observed (Al-Salim et al, 2011;Corredor et al, 2009;Huang et al, 2011;Hussain et al, 2013;Marchiol et al, 2014;Wang et al, 2012b). Pits equipped with pit membranes in the tracheids mainly limit NP transport in the xylem vasculature, and primary pit fields in sieve areas are the bottlenecks of the phloem sieve cells (Fahn, 1982;Raven, 2003).…”
Section: Vasculaturementioning
confidence: 99%
“…From the xylem, NPs can distribute within the rest of the plant and be loaded into the phloem. Nanoparticles in the xylem have often been observed (Al-Salim et al, 2011;Corredor et al, 2009;Huang et al, 2011;Hussain et al, 2013;Marchiol et al, 2014;Wang et al, 2012b). Pits equipped with pit membranes in the tracheids mainly limit NP transport in the xylem vasculature, and primary pit fields in sieve areas are the bottlenecks of the phloem sieve cells (Fahn, 1982;Raven, 2003).…”
Section: Vasculaturementioning
confidence: 99%
“…67 This mechanism has been already described in plants after exposure to different silver nitrate doses. 68 In animals, the intracellular formation of silver nanoparticles was also confirmed after oral exposure to silver ions in rats. 69 This procedure can explain the detection of silver nanoparticles in cytosol of our mucosal samples.…”
Section: Toxic Effects By Silver Ionsmentioning
confidence: 93%
“…The formed AgNPs were densely around chloroplasts of Brassica juncea, which areas were associated with a high content of reducing sugars, and therefore reducing sugars were implicated as the reagents responsible for this reduction [45]. However, another study on the formation of AgNPs in living Brassica juncea, Festuca rubra, and Medicago sativa showed that the contents of reducing sugars and antioxidant com-pounds were quite different among the species, which suggested that it was unlikely that a single substance was responsible for this process [46]. The biosynthesized AgNPs by Chlamydomonas reinhardtii were localized in the peripheral cytoplasm and at one side of flagella root, the site of pathway of adenosine triphosphate transport and its synthesis related enzymes, which provided an evidence for the involvement of oxidoreductive proteins in this reduction process [47].…”
Section: Reduction By Plantmentioning
confidence: 99%